Examination of Antarctic prokaryotic diversity through molecular comparisons - Franzmann, PD (Biodiversity and Conservation, 1996)
Prokaryotes perform key functions in Antarctic ecosystems, and knowledge of the taxonomy of Antarctic prokaryotes is a prerequisite for the transfer of information between fields of scientific inquiry. The taxonomy of prokaryotes has been greatly revised and improved due to the refinements afforded by molecular techniques such as 16S rRNA sequencing. Past inventories of Antarctic microbial diversity are difficult to reconcile with the developing, phylogenetically-based taxonomy.Antarctic prokaryotes are considerably diverse and most evolutionary groups are represented, including representatives of both Archaea and Bacteria. The diversity appears unique due to the ease with which new species can be isolated; however, that may be a result of our vastly incomplete knowledge of both Antarctic and non- Antarctic prokaryotic diversity. Use of the 16S rRNA gene as a molecular clock would suggest that the majority of Antarctic prokaryotes diverged from their nearest known non-Antarctic relatives long before a stable ice-sheet developed in Antarctica. The time of colonization (or recolonization) of Antarctic environments by individual species may have been very recent in evolutionary time scales.